Protein and Anthocyanin Production of Waterleaf Shoots (Talinum triangulare (Jacq.) Willd) at Different Levels of Nitrogen+Potassium and Harvest Intervals - Susanti, Hilda (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
The experiment was conducted at IPB Experimental Station, Leuwikopo, Dramaga, Bogor, from November 2009 until February 2010 to study the effect of different nitrogen+potassium rates and harvest intervals on protein and anthocyanin production of waterleaf shoot (Talinum triangulare (Jacq.) Willd). A randomized complete block design was used with three replications of two factors, which were four N+K dosages (50 kg urea + 50 kg ha-1 KCl, 50 kg urea + 100 kg ha-1 KCl, 100 kg urea + 50 kg ha-1 KCl, 100 kg urea + 100 kg ha-1 KCl) and three harvest intervals (30, 15, and 10 days). The results showed that interaction of 100 kg urea + 100 kg ha-1 KCl and 15-day harvest interval produced the highest content (8.29 mg g-1 fresh weight) and production (4.72 g plant-1) of protein. The interaction of N+K dosages and harvest intervals were not signifi cant in affecting the anthocyanin content. The highest production of anthocyanin was produced by single treatment of 100 kg urea + 100 kg ha-1 KCl (152.23 μmol plant-1) and 10 days harvest interval (165.47 μmol plant-1), respectively. Leaf protein levels negatively correlated with anthocyanin content. Keywords: anthocyanin, fertilizer, harvest interval, protein, Talinum triangulare